Recovering dynamic distortions on output of channel transmitted continuous signals - Ivanyuk, V.A.; Halmuhamedova, F.A. (Математичне та комп'ютерне моделювання. Серія: Технічні науки, 2012)
Встатті розглядаються алгоритми відновлення неперервних сигналів, на які динамічно впливають істотні спотворення у виглядів шумів. Показано, що розроблені алгоритми цифрової фільтрації можна застосувати для стабільної роботи оператора інверсії каналу. Для забезпечення стійкості розв’язку некоректних задач застосовуються методи регуляризації з максимальним використанням додаткової апріорної інформації про сигнал ішум. Приведено результати комп'ютерних експериментів. Signal restoring algorithms, subjected to essential dynamic distortions in channels transmitting continuous signals in conditions of noise availability are considered in this paper. It is shown, that the application of developed algorithms digital filtration made possible to avoid unstable operation of operator inversion of the channel. For maintenance stability of the delivered problem solution with the purpose of maximum use additional a priory information on required signal and noise regularization methods of ill posed problems are used. Some results of computer experiments are shown.